Penggunaan E- Wallet Sebagai Alat Transaksi Pengganti Uang Tunai Bagi UMKM Di Kecamatan Padangsidimpuan Tenggara - Hasibuan, Tondi Agustian; Yarham, M. (CV. ITTC INDONESIA, 2023)
This research aims; to evaluate the role of MSMEs in driving the growth of E-wallets or Digital Wallets in Southeastern Padangsidimpuan District; to analyzethe effects of using E-wallets as a non-cash payment method by MSMEs in Southeastern Padangsidimpuan District. The research respondents consist of 20 MSMEs that use E-walet for data processing. Data is analyzed using statistical formulas, and the research results indicate that MSMEs play a role in increasing the use of E-walet. The use of E-walet seen an increase, and the research also shows that using Digital Wallets as a non-cash payment method helps MSMEs avoid the need for change.